Exploring the Nutraceutical Role of Selenium Nanoparticles on Laying Performance, Egg Attributes and Immune Response in Laying Hens - Malik, Zarnain; Marghazani, Illahi Bakhsh; Chachar, Bahram; Shah, Qurban Ali; Shah, Tahmina; Mengal, Biburg; Ujjan, Nisar Ahmed; Bilal, Muhammad (Indus Journal of Bioscience Research, 2025)
Current study investigated the dose-dependent effects of dietary selenium nanoparticles (SeNPs) supplementation on productive performance, organ development, hematological parameters and humoral immunity of laying hens. A completely randomized design was employed, allocating 120 twenty-week-old White Fayoumi birds to four dietary groups (n=30 per group) receiving 0.0 (control), 0.5, 1.0, or 1.5 mg/kg SeNPs for 12-weeks of experimental period (21 to 32 weeks of age). Results demonstrated a significant (P<0.05) enhancement in live weight gain and FCR in the group supplemented with 1.0 mg/kg SeNPs compared to the control. Similarly, egg production, egg weight, yolk weight, albumen weight, shell thickness, and egg mass were significantly (P<0.05) elevated in this group. Notably, the 1.0 mg/kg SeNPs group exhibited significantly (P<0.05) increased relative weights of all examined organs. Conversely, the 1.5 mg/kg SeNPs group showed a significant (P<0.05) decline in laying performance and FCR relative to the control. While the 1.0 mg/kg SeNPs group displayed improved trends in certain blood biochemical parameters, significant differences (P<0.05) were only observed for hemoglobin levels. Importantly, supplementation with 1.0 mg/kg SeNPs significantly (P<0.05) increased serum IgM and IgA concentrations, whereas the 1.5 mg/kg SeNPs dosage significantly (P<0.05) reduced these immunoglobulin levels. In conclusion, this study elucidates a critical role for SeNPs supplementation in laying hens, with an optimal inclusion level of 1.0 mg/kg significantly improved productivity, organ development, and humoral immunity. However, exceeding this dosage (1.5 mg/kg) resulted in detrimental effects, highlighting the narrow therapeutic window and the importance of precise SeNPs administration in poultry nutrition.